2016
DOI: 10.1177/1535370216650759
|View full text |Cite
|
Sign up to set email alerts
|

Original Research: Influence of okadaic acid on hyperphosphorylation of tau and nicotinic acetylcholine receptors in primary neurons

Abstract: The aim of the study was to investigate the influence of hyperphosphorylation of tau induced by okadaic acid on the expression of nicotinic acetylcholine receptors and the neurotoxicity of b-amyloid peptide. Primary cultures of neurons isolated from the hippocampus of the brains of neonatal rats were exposed to okadaic acid or/and Ab . Tau phosphorylated at Ser404 and Ser202, and the protein expressions of a7, a4 and a3 nAChR subunits were quantified by Western blotting, and their corresponding mRNAs by real-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…Amongst others, it particularly leads to the activation of GSK-3β, neuroinflammation and oxidative stress (Tachibana et al, 1981 ; Hanger et al, 2009b ; Kamat et al, 2013a ; Kamat and Nath, 2015 ; Baker and Götz, 2016 ; Zhao et al, 2016 ). Several in vivo and in vitro studies showed that OA induces tau phosphorylation and is also able to enhance the neurotoxicity of Aβ (Ahn et al, 2016 ; Baker and Götz, 2016 ; Zhao et al, 2016 ). Kamat et al ( 2013b ) reported that intracerebroventricular administered OA into rats impaired memory in the morris water maze.…”
Section: Discussionmentioning
confidence: 99%
“…Amongst others, it particularly leads to the activation of GSK-3β, neuroinflammation and oxidative stress (Tachibana et al, 1981 ; Hanger et al, 2009b ; Kamat et al, 2013a ; Kamat and Nath, 2015 ; Baker and Götz, 2016 ; Zhao et al, 2016 ). Several in vivo and in vitro studies showed that OA induces tau phosphorylation and is also able to enhance the neurotoxicity of Aβ (Ahn et al, 2016 ; Baker and Götz, 2016 ; Zhao et al, 2016 ). Kamat et al ( 2013b ) reported that intracerebroventricular administered OA into rats impaired memory in the morris water maze.…”
Section: Discussionmentioning
confidence: 99%
“…21 Similarly, in a model of neuronal death induced by okadaic acid (OA) that reproduces the typical tau (τ) hyperphosphorylation of Alzheimer's disease, it has been described that this hyperphosphorylation of tau reduces the expression of nAChRs and enhances the neurotoxicity of β-amyloid peptide. 23 In agreement with this fact, the activation of both α7 and β2* nAChR afforded neuroprotection against OA-induced neurotoxicity. 24 Curiously, the promotion of the Ca 2+ entry through the α7 nAChR using an α7-selective positive allosteric modulator (PAM), PNU 120596, did not protect against this OA-evoked neurotoxicity.…”
Section: ■ Introductionmentioning
confidence: 73%
“…It has been reported that OA results in robust tau hyperphosphorylation at multiple pathological epitopes in animal and cell culture studies [ 56 , 58 , 59 , 106 108 ]. It is widely established that PP2A is the primary enzyme responsible for dephosphorylation of tau protein throughout the brain, controlling all tau phosphorylation sites.…”
Section: Discussionmentioning
confidence: 99%